PROBLEMS OF PUBLIC SERVICE IN THE REPUBLIC OF UZBEKISTAN: FURTHER IMPROVEMENT OF THE PUBLIC SERVICE SYSTEM (TSUL LEGAL REPORT, 2026)
This article is devoted to the study of the public service system. The author comes to the conclusion that the effectiveness of the public service, its social usefulness is determined by how, in what way and how well it serves the needs of a person, helps them in life. The civil service includes a necessary and important element of the structure of the state. It plays a bridging role between the state and society. This article also analyzes the new draft law “On the State Civil Service”. The further democratization of state building is a continuous process. Obviously, the reform of national statehood in Uzbekistan should also affect the institution of public service. The state program for the implementation of the Strategy of  New Uzbekistan for 2022-2026, approved by the Decree of the President of the Republic of Uzbekistan dated January 28, 2022 №PQ-60, provides new changes in this sphere.